Imaging the large‐scale and cellular response to focal traumatic brain injury in mouse neocortex - Yelena Bibineyshvili; Thomas J. Vajtay; Shiva Salsabilian; Nicholas Fliss; Aastha Suvarnakar; Jennifer Fang; Shavonne Teng; Janet Alder; Laleh Najafizadeh; David J. Margolis (Experimental Physiology)
Abstract Traumatic brain injury (TBI) affects neural function at the local injury site and also at distant, connected brain areas. However, the real‐time neural dynamics in response to injury and subsequent effects on sensory processing and behaviour are not fully resolved, especially across a range of spatial scales. We used in vivo calcium imaging in awake, head‐restrained male and female mice to measure large‐scale and cellular resolution neuronal activation, respectively, in response to a mild/moderate TBI induced by focal controlled cortical impact (CCI) injury of the motor cortex (M1). Widefield imaging revealed an immediate CCI‐induced activation at the injury site, followed by a massive slow wave of calcium signal activation that travelled across the majority of the dorsal cortex within approximately 30 s. Correspondingly, two‐photon calcium imaging in the primary somatosensory cortex (S1) found strong activation of neuropil and neuronal populations during the CCI‐induced travelling wave. A depression of calcium signals followed the wave, during which we observed the atypical activity of a sparse population of S1 neurons. Longitudinal imaging in the hours and days after CCI revealed increases in the area of whisker‐evoked sensory maps at early time points, in parallel to decreases in cortical functional connectivity and behavioural measures. Neural and behavioural changes mostly recovered over hours to days in our M1‐TBI model, with a more lasting decrease in the number of active S1 neurons. Our results in unanaesthetized mice describe novel spatial and temporal neural adaptations that occur at cortical sites remote to a focal brain injury.